Perlindungan Hukum Pemenang Lelang Eksekusi Barang Rampasan Negara Yang Berstatus Objek Jaminan Fidusia - Abikul Halik; Djoni Sumardi Gozali (Jurnal Riset Rumpun Ilmu Bahasa, 2025)
Auctions in Indonesia serve a dual function not only as a mechanism for buying and selling to obtain optimal prices, but also as a legal enforcement tool that reflects both the public and private aspects of the auction process. This study aims to analyze the legal standing of the auction minutes deed (akta risalah lelang) in providing legal certainty for auction winners, particularly concerning ownership of vehicles resulting from the execution of state-confiscated assets. This study employs a normative approach, which examines law as a set of norms applicable within society and functions as a guideline for individual behavior. In this context, the auction minutes deed is regarded as an authentic deed; however, its existence does not automatically serve as legitimate proof of ownership for the winning bidder. Nevertheless, the deed still ensures legal certainty by demonstrating the good faith of the buyer and can serve as the legal basis for transferring vehicle ownership documents, proof of the sales transaction, and valid legal evidence.